2013
DOI: 10.1016/j.molcel.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

OTULIN Restricts Met1-Linked Ubiquitination to Control Innate Immune Signaling

Abstract: Conjugation of Met1-linked polyubiquitin (Met1-Ub) by the linear ubiquitin chain assembly complex (LUBAC) is an important regulatory modification in innate immune signaling. So far, only few Met1-Ub substrates have been described, and the regulatory mechanisms have remained elusive. We recently identified that the ovarian tumor (OTU) family deubiquitinase OTULIN specifically disassembles Met1-Ub. Here, we report that OTULIN is critical for limiting Met1-Ub accumulation after nucleotide-oligomerization domain-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
285
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 227 publications
(299 citation statements)
references
References 39 publications
13
285
1
Order By: Relevance
“…RIP2 was later uncovered to be the prime substrate of LUBAC in NOD2 signaling through quantitative proteomics analysis of the components obtained from M1-Ub-affinity purification. 21 Although the UBD of TAB2/3, specifically the NZF domain, preferentially binds to K63-type chains, the UBD in NEMO, referred to as UBAN (ubiquitin binding in ABIN and NEMO), binds significantly more strongly to M1 chains compared with K63 chains. Thus, the synchronous addition of K63-and M1-linked chains on RIP2 may provide an optimal platform to facilitate the TAK1-catalyzed activation of the IKK complex.…”
Section: Modulation Of Innate Immune Signaling By the Ubiquitin Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…RIP2 was later uncovered to be the prime substrate of LUBAC in NOD2 signaling through quantitative proteomics analysis of the components obtained from M1-Ub-affinity purification. 21 Although the UBD of TAB2/3, specifically the NZF domain, preferentially binds to K63-type chains, the UBD in NEMO, referred to as UBAN (ubiquitin binding in ABIN and NEMO), binds significantly more strongly to M1 chains compared with K63 chains. Thus, the synchronous addition of K63-and M1-linked chains on RIP2 may provide an optimal platform to facilitate the TAK1-catalyzed activation of the IKK complex.…”
Section: Modulation Of Innate Immune Signaling By the Ubiquitin Systemmentioning
confidence: 99%
“…The linear ubiquitin chain-specific DUB OTULIN binds to the catalytic LUBAC subunit HOIP and selectively trims the M1-linked chains from RIP2, thereby attenuating NOD2 signaling. 21 In addition, HOIP also interacts with CYLD, which limits the extension of both K63-and M1-linked chains on RIP2 to restrict NOD2 signaling. 22 …”
Section: Modulation Of Innate Immune Signaling By the Ubiquitin Systemmentioning
confidence: 99%
“…RIPK2 plays a central role in the NOD signalling pathway and cells deficient in RIPK2 fail to mount a cytokine response upon NOD stimulation 14,15 . We and others have shown that upon NOD stimulation, RIPK2 is ubiquitylated by inhibitor of apoptosis (IAP) proteins, and this recruits the linear ubiquitination assembly complex (LUBAC), which is essential for downstream signalling [16][17][18] .…”
mentioning
confidence: 99%
“…Met1-Ub chains are assembled by the linear ubiquitin chain assembly complex (LU-BAC), composed of HOIP, HOIL-1, and SHARPIN [1]. LUBAC function is regulated by the deubiquitinases (DUBs) OTULIN [2-4] and CYLD [5][6][7], which both associate with the catalytic subunit HOIP [5][6][7][8].Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%
“…Previous studies have revealed that OTULIN exclusively hydrolyzes Met1-Ub, prevents accumulation of Met1-Ub on LUBAC components under basal conditions, and restricts ubiquitination of LUBAC substrates after receptor stimulation [2][3][4]. However, the contribution of OTULIN to regulation of physiological immune responses had not been investigated.…”
mentioning
confidence: 99%